Principles and practices of small-scale sport event management (IGI Global, 2020)
Description: Although there is significant research on large events that take place within athletics, small-scale events are largely ignored, in part due to the lack of press that they generate. However, these events require planning and preparation in the same way that larger sporting events do. This disparity between the effort that goes into the event and the attention the event draws allows for a gap in strategy or information available to those planning smaller scale athletic events.